AmF/NaF/SnCl2 solution reduces in situ enamel erosion - profilometry and cross-sectional nanoindentation analysis - Thayanne Monteiro RAMOS-OLIVEIRA; Camila Vieira SILVA; Paula Mendes Acatauassu NUNES; Cecília Pedroso TURSSI; Peter RECHMANN; Patricia Moreira de FREITAS (Sociedade Brasileira de Pesquisa Odontológica, 2017)
Abstract This in situ study aimed to investigate the effect of a tin-containing fluoride solution in preventing enamel erosion. Also, its effects on the partly demineralized zone were assessed for the first time. Thirteen volunteers participated in this 2-phase study, wearing removable intra-oral appliances containing four sterilized bovine enamel slabs, for 8 days, where 2 treatment protocols were tested using samples in replicas (n = 13): CO - no treatment (negative control) and FL - AmF/NaF/SnCl2 solution (500 ppm F-, 800 ppm Sn2+, pH = 4.5). Samples were daily exposed to an erosive challenge (0.65% citric acid, pH 3.6, 4 min, 2x/day). In the 2nd phase, volunteers switched to the other treatment protocol. Samples were evaluated for surface loss using a profilometer (n = 13) and a cross-sectional nanohardness (CSNH) test (n = 13) was carried out in order to determine how deep the partly demineralized zone reaches below the erosive lesion. The data were statistically analyzed by two-way ANOVA. Erosive challenges lead to smaller enamel surface loss (p < 0.001) in the FL group when compared to group CO. Data from CSNH showed that there was no significant difference in demineralized enamel zone underneath erosion lesions between the groups. An amorphous layer could be observed on the surface of enamel treated with tin-containing solution alone. Under the experimental conditions of this in situ study, it can be concluded that AmF/NaF/SnCl2 solution prevents enamel surface loss but does not change the hardness of the partly demineralized zone near-surface enamel.